Pharmacists' roles in emergency and disasters: COVID-19 as an example - Wejdan Aburas; Thamir M. Alshammari (Elsevier, 2020)
Background: Emergencies and disasters are major threats to health care systems. Coronavirus Disease 2019 (COVID-19) is at the center of a recent emergency situation that requires increased attention from health care professionals, including pharmacists. This study was aimed at providing an overview of pharmacists' roles in disasters and formulating a definition of expected roles and tasks through which they can perform these roles properly. Methods: A systematic review was conducted utilizing a literature search performed on the Medline, EMBASE and PubMed databases. The last search occurred on 14 July 2020. Data were extracted and recorded on a data extraction sheet by the reviewers, then categorized using the prevention, preparedness, response, and recovery (PPRR) model. Study quality was evaluated using the Critical Appraisal Skills Program (CASP) checklist. Results: Fifteen articles addressing pharmacists' roles in disasters were included. Of these, three addressed pharmacists' roles during the COVID-19 pandemic. Pharmacists' roles in the prevention of emergencies, including COVID-19, are focused on chronic disease medication supply and education. Regarding pharmacists' preparedness to perform their roles in disasters, they were more focused on health policy and population health planning, especially regarding the COVID-19 pandemic. Direct patient care continues to support patients through medication availability, and pharmacists' clinical roles are examples of their response to disasters. In addition, pharmacists have an important role in disaster recovery that involves several activities, such as restocking emergency kits and reestablishing normal stock. Studies were generally of a reasonable quality. However, some limitations were noted among studies, and higher quality studies that contribute to existing knowledge are needed. Conclusion: Health care systems' utilization of pharmacists' new roles can result in a well-prepared disaster response, as observed during the COVID-19 pandemic. Pharmacists' engagement in decision-making processes and adequate demonstration of pharmacists' nontraditional roles in the literature can facilitate the health care community's acceptance of such roles.